Effects of pre-treated crumb rubber as sand partial replacement on compressive strength of Engineered Cementitious Composites (ECC) / Atiqah Abdul Aziz… [et al.] - Abdul Aziz, Atiqah; Rozli@Rosli, Mohd Ikmal Fazlan; Abd Ghani, Kay Dora; Zakaria, Noorliyana (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
This study was conducted to determine the surface morphology of crumb rubber (CR) treated with 10% Sodium Hydroxide (NaOH) solution at different periods and the compressive strength of the treated rubberised engineered cementitious composites (R-ECC). R-ECC is a type of engineered cementitious Composite (ECC) with CR as partial sand replacement. In contrast to the quasi-brittle nature of conventional concrete, engineered cementitious Composite (ECC) is distinguished for its tensile strain-hardening behaviour and tensile ductility. However, adding crumb rubber (CR) in ECC as partial sand replacement reduces the composites’ compressive strength owing to its smooth surface. The Scanning Electron Microscopy (SEM) test was conducted on the CR samples, which had been treated with 10% NaOH for 1, 2 and 3 days. Meanwhile, the compressive strength test was conducted on 45 cubes consisting of standard ECC, untreated R-ECC and treated R-ECC. The results discovered that 2 and 3 days of 10% NaOH treatment on CR enhanced its surface roughness, and 2 days NaOH treated R-ECC is the optimum duration for the highest compressive strength reduction. Therefore, the enhanced surface roughness of the CR used as partial sand replacement in the ECC can lessen the compressive strength reduction owing to better bonding between CR and cement matrix in the composites.